Synthesis of Acid Dyes Based on 4-Hydroxy-1-Phenyl-2-Oxoquinoline System and Their Application - Mehta, H.T.; Mehta, A.G. (Asian Journal of Chemistry, 2010)
4-Hydroxy-1-phenyl-2-oxoquinoline (HPOQ) used as coupling component was synthesised by the condensation of o-chlorobenzoic acid and aniline, followed by acetylation and ring closure. Some new azo dyes were prepared by coupling HPOQ with various diazo components. Dyeing properties of these dyes on silk, wool and nylon were assessed. The percentage exhaustion of dye-bath on silk, wool and nylon was 58-74%, 66-80% and 57-69% respectively. A study of the fastness of dyed patterns showed that dyes were good on silk and wool and fair for nylon.